THE APPLICATION OF THE SFAS NO.45 ON FINANCIAL REPORTING IN THE NON-PROFIT ORGANIZATION NURUL HUDA MOSQUE KAWANGKOAN - Mangkona, Sri Wardana Saleh; Walandouw, Stanley Kho (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Organization are founded by the public due to the similarity of interests, both in the realization of human nature as well as to meet their needs. Based on the objectives, the organization can be divided into non-profit organizations and commercial organizations. There is a fundamental difference between nonprofit organizations and commercial organizations, the IAI makes SFAS No.45 which regulates the financial statements of non-profit organizations. The purpose of this study is to see whether the application of financial reporting at Masjid Nurul Huda Kawangkoan is in accordance with what is stated in SFAS No.45. The analytical method used is quantitative descriptive to give an overview of the financial reporting system Masjid Nurul Huda Kawangkoan. The results shows the financial statements at Masjid Nurul Huda Kawangkoan is not in accordance with the preparation of the financial statements which are based on the format of the financial statements of nonprofit in SAFS No.45. No form of financial statements report cash receipts and disbursement is in accordance with the understanding of the mosque committee. Mosque officials do not present a statement of financial position, activities, cash flows and notes to the financial statements. The Mosque management should prepare financial statements based on the conditions IAI, as stipulated in SFAS No.45 that financial statement information has qualitative characteristics. Keywords: statement, accounting standards, nonprofit